Business Management Model for the Biochemical Industry - Chotiwong, Chuleewan; Srichompu, Jutamat (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2021)
The objective of this research was to study the biochemical industry business management factors and create the biochemical industry business management model. This study was qualitative and quantitative mixed-method research. The instrument used in this study was the questionnaire and the populations were entrepreneurs, executives, and the biochemical industry staff. The qualitative analysis used content analysis, and the quantitative analysis used frequency, mean, percentage, standard derivation and factor analysis with statistical package. The study of the biochemical industry business management found that entrepreneurs’ potential in the biochemical industry factor included 6 factor loading as 1) work capacity 2) business management 3) law and ethics 4) value added 5) technology and innovation, and 6) power driven. The biochemical industry competition factor included 3 factor loading as 1) competitors and supplier 2) consumers’ behavior, and 3) government policy. The results of factor analysis were created the draft of the biochemical industry business management model for the experts to evaluate. The experts decided a unanimous vote that the biochemical industry business management model was appropriate to apply in the biochemical industry.